Quality of life following Myocardial infection - Amarasekera, S (My University, 1998)
The objective of the study was to compare the quality of life of patients diagnosed as having a myocardial infarction against a control group. Quality of life was determined in respect of physical function. Psychological function and social role function. A random sample of cases was recruited into the study and an age and sex matched control group was selected from persons who had no previous history of myocardial infarction. There was no difference in the quality of life in regard to the basic ADL used in the account of physical function. A significant difference was seen in the quality of life in regard to the intermediate ADL(mean score for the controls and the mean score for the cases in regards to basic ADL being 3.75 and 3.76 and for intermediate ADL being 3.67 and 2.66 respectively).Only 14 per cent of the cases had an intermediate ADL score of over the mean value for the control group. In regard to social role function significant differences were observed between the two study groups. The mean scores for the cases and controls in regard to these being 2.92 and 3.12 for work performance and 2.92 and 3.62 for social activity respectively. It was seen that only 32.7 per cent and 37.3 per cent of the cases had the same or a higher score in work performance and social activity than the controls respectively. It was interesting to note that in the study the cases had a higher quality of life in respect of the quality of interaction and psychological profile than the controls, in spite of their physical and social activity being limited. The mean score for the cases and controls was 5.46 and 4.53 for the quality of interaction and 5.03 and 3.92 reported in the assessment of psychological function